2003
DOI: 10.1080/00223980309600617
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Cooperation in the Five-Factor Model: Individual Differences in Achievement Orientation

Abstract: The authors investigated the relationship between basic achievement orientations of competition and cooperation and the five-factor model of personality as measured by the Revised NEO Personality Inventory (NEO-PI-R; P. T. Costa & R. R. McCrae, 1992). They examined 2 types of competition: hypercompetition (R. M. Ryckman, B. Thornton, & J. C. Butler, 1994) and personal development competition (R. M. Ryckman, M. Hammer, L. M. Kaczor, & J. A. Gold, 1996), as conceptualized by K. Horney (1937). In a sample of 251 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 23 publications
5
84
1
8
Order By: Relevance
“…Research has indicated that hypercompetitive individuals are indeed highly neurotic and that these neurotic tendencies are based in anger and hostility toward others (Ross, Rausch, & Canada, 2003). In addition, they evidence other negative, unhealthy personality and social characteristics including low self-esteem, high anxiety, narcissism, dogmatism, a need to control and dominate, strategically manipulate self-impressions, and Machiavellianism (Dru, 2003;Ryckman, Hammer, Kaczor, & Gold, 1990;Ryckman, Libby, van den Borne, Gold, & Lindner, 1997;Ryckman, Thornton, & Butler, 1994;Ryckman, Thornton, Gold, & Burckle, 2002;Thornton, Lovley, Ryckman, & Gold, 2009;Watson, Morris, & Miller, 1998).…”
Section: Hypercompetitive Orientationmentioning
confidence: 99%
“…Research has indicated that hypercompetitive individuals are indeed highly neurotic and that these neurotic tendencies are based in anger and hostility toward others (Ross, Rausch, & Canada, 2003). In addition, they evidence other negative, unhealthy personality and social characteristics including low self-esteem, high anxiety, narcissism, dogmatism, a need to control and dominate, strategically manipulate self-impressions, and Machiavellianism (Dru, 2003;Ryckman, Hammer, Kaczor, & Gold, 1990;Ryckman, Libby, van den Borne, Gold, & Lindner, 1997;Ryckman, Thornton, & Butler, 1994;Ryckman, Thornton, Gold, & Burckle, 2002;Thornton, Lovley, Ryckman, & Gold, 2009;Watson, Morris, & Miller, 1998).…”
Section: Hypercompetitive Orientationmentioning
confidence: 99%
“…Hypercompetitiveness manifests in an indiscriminant need to compete and succeed at any cost as a neurotic means of maintaining and enhancing one's self-esteem. It is characterized by low self-esteem, narcissism, suspicion, hostility and aggressiveness toward others and a predisposition to be controlling, manipulative and exploitive of others and more (Burckle et al, 1999;Collier et al, 2010;Dru, 2003;Kaczor et al, 1991;Ross et al, 2003;Ryckman et al, 1990;1997;Thornton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is likely that competition avoiders would not act in a straightforward or trustworthy manner with others, (Ross et al, 2003) key facets of agreeableness. Indeed, Horney (1973) pointed out that competition avoiders may characteristically feel a keen sense of inferiority and harbor antisocial feelings that they try to conceal from others.…”
Section: Introductionmentioning
confidence: 99%
“…And coopetition is often regarded as an immanent element of corporate growth strategy (Dagnino, 2009). There are also analyses of simultaneous streams of cooperation and competition at the internal organisational level, in particular in transnational corporations (Luo, 2005;Luo et al 2006;Slotegraaf and Tsai, 2002), individual people (Colley et al, 1985;Lu and Argyle, 1991;Simmons et al 2001;Ross et al 2003;Geraudel and Salvetat, 2014) and networks (Cygler 2010;Madhavan, 2006, 2001;Bengtsson and Kock, 2000).…”
Section: The Coopetition Conceptmentioning
confidence: 99%